Cord blood chimerism and relapse after haplo-cord transplantation. Issue 2 (1st February 2017) - van Besien, Koen; Koshy, Nebu; Gergis, Usama; Mayer, Sebastian; Cushing, Melissa; Rennert, Hannah; Reich-Slotky, Ronit; Mark, Tomer; Pearse, Roger; Rossi, Adriana; Phillips, Adrienne; Vasovic, Liljana; et al.
Abstract: Haplo-cord stem cell transplantation combines the infusion of CD34 selected hematopoietic progenitors from a haplo-identical donor with an umbilical cord blood (UCB) graft from an unrelated donor and allows faster count recovery, with low rates of disease recurrence and chronic graft-versus-host disease (GVHD). But the contribution of the umbilical cord blood graft to long-term transplant outcome remains unclear. We analyzed 39 recipients of haplo-cord transplants with acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS), engrafted and in remission at 2 months. Median age was 66 (18–72) and all had intermediate, high, or very-high risk disease. Less than 20% UCB chimerism in the CD33 lineage was associated with an increased rate of disease recurrence (54% versus 11% p < 0.0001) and decrease in one year progression-free (20% versus 55%, p = 0.004) and overall survival (30% versus 62%, p = 0.02). Less than 100% UCB chimerism in the CD3 lineage was associated with increase rate of disease recurrence (46% versus 12%, p = 0.007). Persistent haplo-chimerism in the CD3 lineage was associated with an increased rate of disease recurrence (40% versus 15%, p = 0.009) Chimerism did not predict for treatment related mortality. The cumulative incidence of acute GVHD by day 100 was 43%. The cumulative incidence of moderate/severe chronic GVHD was only 5%. Engraftment of the umbilical cord blood grafts provides powerful graft-versus-leukemia (GVL) effects which protect against disease recurrence and is associated with low risk of chronic GVHD. Engraftment of CD34 selected haplo-identical cells can lead to rapid development of circulating T-cells, but when these cells dominate, GVL-effects are limited and rates of disease recurrence are high.